Physical disability in leprosy patients in Campo Grande - Mato Grosso do Sul - Bernardes, Camila Arantes (2009)
This study aimed to determine the frequency of disability in new cases of leprosy in the municipality of Campo Grande, diagnosed in the period of April 2008 to March 2009, and, characterize the clinical, epidemiological and sociodemographic. Among the 69 cases treated in the period, more than half had some degree of physical disability (59, 4%), whereas 18,8% of cases were detected with GIF II. There is a concentration of cases in the male population (59, 4%) and association between gender and degree of physical disability II with GIF II among men of 24, 1% even was observed in the same fact in multibacillary forms, with 33, 3% of lepromatous with GIF II. The proportion of cases in the population up to 15 years was high (10, 1%) higher than that found in other studies. There was predominance (84, 0%) of people with low education, with the most complete basic education, with per capita income of up to 1,5 minimum wages. As the geographical distribution of cases, there is predominance in the city districts in South and North (65, 1%). The findings of this study show that health professionals and managers should encourage improvements in early diagnosis, assessment of cases and follow up services for the prevention of disability of Hansen‘s disease.